A Prospective Study on Risk Factors and Drug Utilization Review Based on Clinical Profiles in Diabetic Emergency in a Tertiary Care Hospital - Kumar, Avvari Sanjeeva; Ashok, Amatinthala; Anusha, Maddika; Shafeen, Aeman; Methusala, Reddypogu Jona (Indian Journal of Pharmacy Practice)
Background: Diabetic Ketoacidosis (DKA) is a triad of Diabetes, ketosis and metabolic acidosis. Aim: To estimate the risk factors and drug utilization review based on clinical profiles in diabetic emergency (DKA) in a tertiary care hospital prospectively. Objectives: To determine the demographic characters (Gender, Age and Sex), type of diabetics, clinical manifestations, precipitating factors, comorbidities, biochemical parameters and therapeutic drug monitoring parameters like Drug interactions, ADR’s, untreated indications. Methods: A Prospective crosssectional study was conducted on 50 patients in both male and female general medicine units at Government General Hospital, Kurnool. The patients were selected based on the inclusion criteria. Newly diagnosed diabetic patients with Diabetic Ketoacidosis and past history of hospitalization due to occurrence of Diabetic Ketoacidosis were also included in the study. Results: Diabetic Ketoacidosis was seen in both types I and type II diabetes. Among the study population female patients were higher in number. Presentation of Diabetic ketoacidosis was higher among the type II diabetes. Diabetic Ketoacidosis among adults was more common amongst the patients in age groups of 30-40 and 50-60 years of age. Nausea, vomiting and shortness of breath were the most common presenting complaints. Most common precipitating factors include Drug Incompliance and Infection. Random blood sugar levels were more than 300 mg/dL in majority of patients. The treatment had seven adverse drug reactions and nine untreated indications in the study. Conclusion: Most common precipitating factors include Drug Incompliance (32%) and Infection.
Keywords: Diabetes; Diabetic Ketoacidosis; Drug utilization review; Drug incompliance; Precipitating Factors and Therapeutic drug monitoring.